ANALISIS PENGARUH PROFITABILITAS DAN PERTUMBUHAN PENJUALAN TERHADAP HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA INDUSTRI FOOD AND BEVERAGE DI BEI PADA TAHUN 2018-2020 - Bayu Cahya Wardani; Dihin Septyanto (CV. Adiba Aisha Amira, 2024)
This study aims to analyze whether profitability and sales growth have an influence on stock prices with capital structure as an intervening variable in the food and beverage industry in 2018-2020. This study uses causal associative research, namely research that aims to determine the effect of two or more variables. The data collection technique in this study uses a documentation study, the authors analyze documents on the IDX official website www.idx.co.id and literature studies by studying, reviewing, and reviewing related literatures in the form of books, journals, news, and blog articles. with the problem under study. The population in this study are food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. With a total of 33 companies. The sample in this study amounted to 18 companies taken using purposive sampling method. The data analysis technique used descriptive analysis and path analysis. From the research results show that profitability has a positive and significant effect on stock prices, sales growth has no effect on stock prices, capital structure has a positive and significant effect on stock prices. profitability has a negative and significant effect on capital structure, sales growth has no effect on capital structure, and capital structure successfully mediates profitability and sales growth on stock prices.